Dampak Kebijakan Agraria Pemerintah Kolonial Belanda terhadap Kondisi Sosial Ekonomi Petani di Pulau Jawa, 1870-1940 - Zulyanti, Mutiara; Zuriatin, Zuriatin; Syahbuddin, Syahbuddin; Hidayat, A. Gafar (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This study examines the impact of Dutch colonial agrarian policies and the socioeconomic conditions of farmers on the island of Jawa during the period 1879–1940, with a focus on the implementation of the Agrarische Wet 1870 and the domein verklaring principle, which transformed land into a commodity and farmers into laborers without sovereignty. Using historical research methods including heuristics, source criticism, interpretation, and historiography, this study utilizes colonial archives, official documents, and secondary literature. Weber’s sociological “Verstehen” approach is employed to analyze the policy’s impact on class, status, and power dimensions within the social structure of colonial villages. The results of the study show that although it formally recognized customary rights, this policy legitimized the seizure of uncertified land from the people and leased it to foreign private companies for up to 75 years. As a result, farmers lost access to land, experienced proletarianization, became trapped in debt, and were forced to work for low wages on plantations. Land liberalization strengthened foreign capital dominance, triggered socioeconomic inequality, and gave rise to various forms of resistance, ranging from open rebellion to sabotage. This study concludes that colonial agrarian policies not only transformed the economic structure but also eroded social cohesion and peasant sovereignty, leaving a legacy of deep agrarian inequality in Jawa.